Manufacturing automation : metal cutting mechanics, machine tool vibrations, and CNC design - Altintas, Yusuf, 1954- (Cambridge : Cambridge University Press, 2012)
'Metal cutting is a widely used method of producing manufactured products. The technology of metal cutting has advanced considerably along with new materials, computers, and sensors. This new edition treats the scientific principles of metal cutting and their practical application to manufacturing problems. It begins with metal cutting mechanics, principles of vibration, and experimental modal analysis applied to solving shop floor problems. Notable is the in-depth coverage of chatter vibrations, a problem experienced daily by manufacturing engineers. The essential topics of programming, design, and automation of CNC (computer numerical control) machine tools, NC (numerical control) programming, and CAD/CAM technology are discussed. The text also covers the selection of drive actuators, feedback sensors, modeling and control of feed drives, the design of real time trajectory generation and interpolation algorithms, and CNC-oriented error analysis in detail. Each chapter includes examples drawn from industry, design projects, and homework problems. This book is ideal for advanced undergraduate and graduate students, as well as practicing engineers'--Provided by publisher.
Machine generated contents note: 1. Introduction; 2. Mechanics of metal cutting; 3. Structural dynamics of machines; 4. Machine tool vibrations; 5. Technology of manufacturing automation; 6. Design and analysis of CNC systems; 7. Sensor-assisted machining; A. LaPlace and z Transforms; B. Off-Line and On-Line Parameter Estimation with Least Squares.
Includes bibliographical references and index.
Keywords: Machining -- Automation; Machine-tools -- Vibration; Machine-tools -- Numerical control